Manajemen Produksi Self-Propelled Mortar Carrier System dalam Mendukung Kemandirian Industri Pertahanan (Studi Kasus PT. SAS Aero Sishan) - Siti Hannah Padliyyah; Syaiful Anwar; Aris Sarjito; Hikmat Zakky Almubaroq (CV. AFDIFAL MAJU BERKAH, 2024)
This research examines the production management of self-propelled mortar carrier systems in supporting the independence of Indonesia's defense industry. In accordance with the Law of the Republic of Indonesia No. 16 of 2012 on Defense Industry which aims to ensure that the fulfillment of defense and security equipment can be carried out independently. This research uses the theory of production and production management presented by E.L. Brech. The production system starts from inputs, which consist of information, management, equipment and workers, as well as raw materials and capital, which then get treatment in the form of transformation into outputs in the form of goods and services. This research uses a qualitative research method with a case study approach. Primary data is obtained through interviews and direct observation to related parties, while secondary data is obtained from literature studies, documents and other data. This research reveals that the production process at PT SAS Aero Sishan still requires improvement efforts to increase production effectiveness. This research underlines the importance of production management to optimize the resources owned through the production process so as to produce quality and superior products and services in order to realize the independence of the defense industry.